Effect of Accessions and Environment Conditions on Coumarin, O-Coumaric and Kaurenoic Acids Levels of Mikania laevigata - Agostini-Costa, Tânia da Silveira; Gomes, Ismael Silva; Fonseca, Maira Christina Marques; Alonso, Araci Molnar; Pereira, Rita de Cassia Alves; Montanari Junior, Ilio; da Silva, Joseane Padilha; Pereira, Ana Maria Soares; da Silva, Dijalma Barbosa; Vieira, Roberto Fontes; Vaz, Ana Paula Artimonte (Planta Medica, 2016)
Coumarin, o-coumaric, and kaurenoic acid are bioactive compounds usually found in the leaves of Mikania laevigata. Genetic and environmental variations in the secondary metabolites of plants may have implications for their biological effects. Three different accessions of M. laevigata cultivated in four sites between the Equator and the Tropic of Capricorn in Brazil were evaluated aiming to present potential raw materials and discuss relationships among these three bioactive compounds. The results revealed effects of plant accessions and environmental factors and suggested two contrasting chemical phenotypes of M. laevigata. The first phenotype presented the highest levels of kaurenoic acid (2283 ± 316 mg/100 g) besides lower levels of coumarin (716 ± 61 mg/100 g), which was also stimulated by the environment and mild climate at the site nearest to the Tropic of Capricorn. The other phenotype presented the lowest levels of kaurenoic acid (137 ± 17 mg/100 g) besides higher levels of coumarin (1362 ± 108 mg/100 g), which was also stimulated by the environment and tropical climate at the site nearest to the Equatorial beach.
Keywords: Mikania laevigata; Asteraceae; metabolism variability; weather variability; geographic variability